Formulation and Inhibiting Activity of Paper Soap Yogurt Whey with Natural Dye of Hylocereus polyrhizus Skin Against Staphylococcus aureus - Estikomah, Solikah Ana; Kautsar, Alfia Manda Putri; Widyaratna, Indri; Muryani, Eni; Ardiyanti, Dwi (BIOEDUSCIENCE, 2025)
Background: Yogurt is a product of fermented cheese liquid waste, which is known to contain lactoferrin, which functions as an antimicrobial. Whey-based yogurt has not been used as an ingredient in making paper soap. This study aims to determine the formula and evaluation of paper soap with the addition of whey yogurt with natural dyes from Hylocereus polyrhizus skin. Methods: This study is an experimental study. The preparation of liquid soap from whey yogurt with natural dyes from red dragon fruit skin (Hylocereus polyrhizus) was made into four whey yogurt formulas with concentrations of 25%, 50%, 75%, and 100%. Product quality includes organoleptic values, pH values, foam height, and alkali antibacterial activity test against Staphylococcus aureus using the Disk Disk method. Results: The results showed that all formulas of Paper soap whey yogurt with dragon fruit (Hylocereus polyrhizus) skin dye showed good physicochemical characteristics, pH 9.0–11 (ASTM 9-11 requirements), foam content 41.7–52.5, and free alkali content 0.02–0.04. Paper soap whey yogurt formula with dragon fruit (Hylocereus polyrhizus) skin dye produced an inhibitory power of 11.27–29.6, including the medium and strong categories. Conclusions: The best formula for Paper soap whey yogurt with dragon fruit (Hylocereus polyrhizus) skin dye is soap with raw material whey yogurt of 75% whey 25% fresh cow's milk. The results of this study indicate that Paper soap whey yogurt with dragon fruit (Hylocereus polyrhizus) skin dye has the potential as a natural antiseptic soap.